Coexistence of fibromyalgia and metabolic syndrome in females: The effects on fatigue, clinical features, pain sensitivity, urinary cortisol and norepinephrine levels: A cross-sectional study - KESKİN, YAŞAR; KESKİN, Yaşar; KÜÇÜKAKKAŞ, OKAN; Nas, Kemal; YURDAKUL, OZAN VOLKAN; Kilic, Erkan; Sargin, Betul; Kasman, Sevtap Acer; Alkan, Hakan; Sahin, Nilay; CENGİZ, GİZEM; Cuzdan, Nihan; et al. (My University, 2021)
Objectives: This study aims to evaluate the coexistence of metabolic syndrome (MetS) and fibromyalgia syndrome (FMS) and determine the effects of this coexistence on neuroendocrine levels and clinical features of FMS.